Earlier Age of First Exposure to Competitive Fighting Has an Adverse Impact on Neuropsychiatric Symptoms and Brain Volume. (4th January 2022) - Bryant, Barry; Narapareddy, Bharat; Char Bray, Michael Johnathan; Richey, Lisa N.; Krieg, Akshay D.; Shan, Guogen; Peters, Matthew; Bernick, Charles
Abstract : Objective: The objective of this study was to determine whether individuals who began fighting competitively at a younger age experienced adverse brain health outcomes compared to fighters who began competing at an older age. Background: Established literature has made clear that fighting sports such as boxing and mixed martial arts can lead to head injury. Prior work from this group on the Professional Fighters Brain Health Study (PFBHS) found that exposure to repetitive head impacts is associated with lower brain volumes and decreased processing speed in fighters. Design/Methods: As part of the PFBHS, current and previously licensed professional fighters were recruited, divided into active and retired cohorts, and matched with a control group that had no prior experience in sports with likely head trauma. This present study examined the relationship between age of first exposure (AFE) to fighting sports and brain structure (MRI regional volume), cognitive performance (CNS Vital Signs, iComet C3), and clinical neuropsychiatric symptoms (PHQ-9, Barratt Impulsiveness Scale). Results: Brain MRI data showed significant correlations between earlier AFE and smaller bilateral hippocampal and posterior corpus callosum volumes for both retired and active fighters. Earlier AFE in active fighters was correlated with decreased processing speed and decreased psychomotor speed. Retired fighters showed a correlation between earlier AFE and higher measures of depression and impulsivity. Conclusions: The findings of this study help to inform clinicians, governing bodies, parents, and athletes of the risks associated with beginning to compete in fighting sports at a young age.